Histological Effects of the Combined Administration of Eldecalcitol and a Parathyroid Hormone in the Metaphyseal Trabeculae of Ovariectomized Rats. (March 2019) - Hasegawa, Tomoka; Yamamoto, Tomomaya; Sakai, Sadaoki; Miyamoto, Yukina; Hongo, Hiromi; Qiu, Zixuan; Abe, Miki; Takeda, Satoshi; Oda, Kimimitsu; de Freitas, Paulo Henrique Luiz; Li, Minqi; Endo, Koichi; et al.
Summary: Intermittent administration of human parathyroid hormone (1-34) (hPTH(1-34)) promotes anabolic action in bone by stimulating bone remodeling, while eldecalcitol, an analog of active vitamin D3, suppresses osteoclastic bone resorption, and forms new bone by minimodeling. We have examined the biological effects of combined administration of eldecalcitol and hPTH(1-34) on 9-week-old Wistar rats that underwent an ovariectomy (OVX) or Sham operation. They were divided into a Sham group, OVX with vehicle (OVX group), OVX with 10 µg/kg/day of hPTH(1-34) (PTH group), OVX with 20 ng/kg/day of eldecalcitol (eldecalcitol group) or OVX with 10 μg/kg/day of hPTH(1-34), and 20 ng/kg/day of eldecalcitol (combined group) for 4 or 8 weeks. As a consequence, the combined group showed a marked increase in bone volume/tissue volume (BV/TV), trabecular thickness (Tb.Th), and trabecular number (Tb.N) than OVX and had the highest bone mineral density (BMD) compared with other groups. OVX and PTH groups exhibited a high osteoblastic surface/bone surface (Ob.S/BS), mineral apposition rate (MAR), and bone formation rate/bone surface (BFR/BS) indices and many TRAP-reactive osteoclasts. Contrastingly, eldecalcitol and combined groups tended to attenuate the indices of osteoclastic surface/bone surface (Oc.S/BS) and Ob.S/BS than that the other groups. The combined group revealed histological profiles of minimodeling- and remodeling-based bone formation. Thus, the combined administration of eldecalcitol and hPTH(1-34) augments their anabolic effects by means of minimodeling and remodeling.